Platelet Activation is a Risk Factor for Obesity - (:unkn) unknown (TURKIYE KLINIKLERI, 2020)
Objective: Obesity is known to be a triggering factor for many chronic diseases. Blood parameters, especially platelet (PLT)-related factors, have gained importance for a better understanding of obesity. In this study, we investigated the correlation between PLT-related parameters and bodily factors to enhance our knowledge of this important area of research. Material and Methods: Consenting volunteers between 18 and 65 years were included in the study. Their heights, weights, body mass indices (BMI), fat percentages, fat masses (FM), and fat-free masses (FFM) were determined. Fat mass index (FMI=fat mass/height m(2)) and fat-free mass index (FFMI=fat free mass/height m(2)) were calculated. Blood samples were taken to determine the parameters such as PLT, mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT). Results: In males, PLT increased with weight, fat percentage, FM, and FMI. However, there was no change in PCT values with these parameters. In females, PLT decreased with age, increased with weight, BMI, fat percentage, FM, FFM, and FMI. PCT increased with weight, BMI, fat percentage, FM, FFM, and FMI. Conclusion: A significant relationship between PLT activation and body fat content was observed in both genders in the present study. Thus, these blood parameters can be a useful tool for investigating inflammation-related complications in obese individuals. It is speculated that obese individuals may be encouraged toward becoming thrombocyte apheresis donors to reduce their PLT counts, which may lead to a decrease in the risk of obesity-related inflammation in such individuals.
Keywords: Obesity; fat mass; fat mass index; platelet; plateletcrit; DISTRIBUTION WIDTH; METABOLIC SYNDROME; VOLUME; COUNT; INDEXES; INFLAMMATION; ASSOCIATION; ADIPOSITY; GLUCOSE; MARKER